Conflict and learning in inter-organizational online communities: negotiating knowledge claims. Issue 5 (2nd September 2014) - Ferguson, Julie; Taminiau, Yvette
Abstract : Purpose: – The purpose of this article is to analyze how learning occurs in inter-organizational online communities, despite highly diverse even conflicting knowledge claims among participants. Design/methodology/approach: – We compared two inter-organizational communities in the domain of development aid through inductive qualitative case study. Findings: – We found that diverse communities proved more likely to yield conflicting knowledge claims in terms of expertise, value consensus and formal position. However, they were also better positioned for enabling mutual learning, than communities with a more uniform representation. Research limitations/implications: – We provide theoretical insights for knowledge management by showing how the negotiation of knowledge claims facilitates mutual learning in inter-organizational online communities. Practical implications: – The findings are practically relevant for managers of knowledge-intensive organizations by showing how knowledge is shared in diverse online communities. The research also shows that the recognized challenges which diverse communities can yield are likely to be outweighed by their benefits: enabling mutual learning, generating useful expertise and a stronger negotiating position. Social implications: – The paper conceives of a development approach that is more inclusive of non-dominant perspectives and solutions in decision-making processes, contributing to improved participation of marginalized people in decision-making processes. Originality/value: – We add a new dimension to knowledge management literature, showing how conflict and learning can be a mutually reinforcing process. Contrary to prior knowledge-based views, we found that a diverse community, with a higher concentration of conflicting knowledge claims, facilitated mutual learning more adeptly than a more uniform community. This is important for knowledge management theory and practice because it shows how inter-organizational communities can benefit from heterogeneity, and how conflict can enable and even strengthen mutual learning.